Emotional Intelligence and Study Habits as Predictors of Online Learning Motivation of Students in Filipino - Balano, Claudine Jade Jaralba; Napil, Melissa C. (Journal of Natural Language and Linguistics, 2024)
The study aims to predict the level of emotional intelligence, study habits, and their significant influence on the online learning motivation of students in Filipino. Analysis was conducted on data collected from 251 STEM students in selected public Senior High Schools who still opted for online learning as delivery of instruction. The study used a quantitative research design and applied a descriptive-correlational technique. Meanwhile, the adopted survey questionnaire was validated and used to gather the data needed for the study. Results revealed through weighted mean that the level of emotional intelligence, study habits, and online learning motivation of students in Filipino were high. With the help of regression analysis, results proved that there was a significant relationship among variables. Thus, the study also showed that learners with high levels of emotional intelligence and study habits significantly influenced their motivation to learn in an online environment, which results in academic success. These findings indicate that a strong foundation in emotion and systematic study habits in learning plays a vital role in sustaining motivation and acquiring knowledge online. Therefore, students will be more engaged in an online learning environment and will be encouraged to learn intrinsically when their emotional intelligence and study habits are well-established. School management, teachers, and institutions can use these findings to understand, support, and make interventions for the development of motivation in the modern way of learning in the online world.